The Coming Storm - Kidd, Rob; Illustrated by Orpinas, Jean-Paul (UK Parragon, 2006)
Set sail on the high seas with the young Jack Sparrow and his crew, as they search for the legendary Sword of Cortes
Include illustrations
Keywords: Pirates -- Rescues -- Swords